2018
DOI: 10.1093/nar/gkx1322
|View full text |Cite
|
Sign up to set email alerts
|

RAD51 and RTEL1 compensate telomere loss in the absence of telomerase

Abstract: Replicative erosion of telomeres is naturally compensated by telomerase and studies in yeast and vertebrates show that homologous recombination can compensate for the absence of telomerase. We show that RAD51 protein, which catalyzes the key strand-invasion step of homologous recombination, is localized at Arabidopsis telomeres in absence of telomerase. Blocking the strand-transfer activity of the RAD51 in telomerase mutant plants results in a strikingly earlier onset of developmental defects, accompanied by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 75 publications
(87 reference statements)
3
21
0
Order By: Relevance
“…The results of both assays demonstrated that neither telomerase expression, nor the activity changes significantly in either of the mutants. These results are consistent with the recently described role of both genes in ALT in A. thaliana (Olivier et al ., ) and indicate that the critical telomere shortening observed in pprtel1 moss lines results from telomere rapid deletion events, rather than from an impaired telomerase function in these mutants.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…The results of both assays demonstrated that neither telomerase expression, nor the activity changes significantly in either of the mutants. These results are consistent with the recently described role of both genes in ALT in A. thaliana (Olivier et al ., ) and indicate that the critical telomere shortening observed in pprtel1 moss lines results from telomere rapid deletion events, rather than from an impaired telomerase function in these mutants.…”
Section: Resultsmentioning
confidence: 90%
“…The results of telomere analyses in pprad51‐1‐2 are consistent with the previous results obtained in corresponding mutants of A. thaliana and with the notion that in the presence of telomerase, RAD51 is not involved in telomere maintenance (Olivier et al ., ). In fact, this also corresponds to the general view of telomeres as recombination‐silent chromosome loci.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Cai et al (2017b) reported the associations between single nucleotide polymorphisms in the RTEL1 gene and stroke risk, and the result showed that the rs6010620, rs6010621, and rs6089953 were associated with an increased risk of stroke. However, Olivier, Charbonnel, Amiard, White, and Gallego () showed RAD51 and RTEL1 gene could compensate telomere loss and protect cell stability when telomere was absent. And another study indicated that the presence of rs6010620 and rs2297440 resulted in a decreased risk of astrocytoma (Jin et al, ).…”
Section: Discussionmentioning
confidence: 99%